Spatial Distribution Pattern and Influencing Factors of Above-Ground Biomass and Species Diversity of Grassland in the Altay Forest Area - Xiaoting Pan; Mao Ye; Qingzhi He; Kaili Zhang (Land, 2023)
Grasslands in the Altay Mountains are the main part of the grassland ecosystem in Xinjiang, and the spatial distribution patterns of grassland species diversity and biomass have changed significantly due to the combined effects of climate change and anthropogenic disturbances. To clarify the effects of point factors on species diversity and biomass, this study investigated the vegetation status of 41 sample plots in the grasslands of the Altay forest area. The Margalef richness index, Simpson dominance index, Shannon–Wiener diversity index, and Alatalo evenness index in the α-diversity measure were used to analyze the changing characteristics of species diversity and to explore the changing patterns of the spatial distribution of species diversity and above-ground biomass. The results show the following: (1) The above-ground biomass of grasslands in the Altay forest area shows a clear spatial pattern, with the above-ground biomass gradually decreasing from northeast to southwest; the altitude gradient shows a “single-peak” pattern of decrease followed by an increase, with the largest biomass at an altitude of 1400–1800 m. (2) There was a significant “bimodal” pattern of variation between above-ground biomass and grassland cover, which was significantly correlated with elevation (p < 0.05) but not with latitude and longitude. (3) Except for the Alatalo evenness index, the trend of the species diversity indexes showed a high trend in the northeast and a low trend in the southwest, with the highest overall species diversity index on average in the Qiaoati sample site. (4) Except for the Alatalo evenness index, all species diversity indexes were significantly correlated with latitude, altitude, longitude, and cover (p < 0.05); the species diversity indexes showed an upward spiral trend with altitude, and with increasing longitude and cover, the species diversity indexes showed an “S” pattern. Elevation, cover, latitude, and longitude were the main environmental factors affecting the spatial patterns of above-ground biomass and species diversity in the grasslands of Altay. The results of the study provide data support for grassland management and maintenance in the Altay forest area, as well as for grassland ecological security in the northwest arid zone of China.